고혈압 한의 진료 실태조사 - 강자연; 강기완; 정민정; 김홍준; 장인수; Kang, Ja-yeon; Kang, Ki-wan; Jeong, Min-jeong; Kim, Hong-jun; Jang, In-soo (대한한방내과학회지, 2016)
Objectives: This study surveyed doctors of Korean medicine on how they treat hypertension in their Korean clinical practices. Methods: An invitation to take an Internet-based questionnaire was sent to doctors who were registered in the Association of Korean Medicine in September 2016. Participants were first asked general profile questions, which included age, gender, work experience as a practitioner, and specialties. Second, they were asked whether they had experience with hypertension treatment and additional questions related to hypertension. Results: A total of 991 replies were received to the questionnaire. Most of the Korean medical doctors (95%) had blood pressure units and had monitored blood pressure. A majority of the Korean medicine doctors (55%) had provided hypertension treatment. Acupuncture and herbal medicine were commonly used for the treatment of hypertensive patients. In addition, bloodletting, moxibustion, pharmacopuncture, cupping, Chuna, Qigong exercise, meditation, and Tai Chi were used. Many doctors also recommended lifestyle modification. The respondents said that Korean medicine improves general health conditions (42.6%) and has low adverse effects (29.9%). One of the most common opinions about the revitalization measures of Korean medicine was expanding health insurance benefits (20.8%). Conclusions: Through this survey, we found out information about the present situation of hypertension treatment in Korean medicine. In the future, it is possible that hypertension treatment using Korean medicine will be demanded and used by practitioners if it is covered by public health insurance.